Role of Faith Based Organizations (FBO’s) in Responding to the Socio-Economic Impact of Covid-19 in Nyakinama Sub-County Kisoro District. - Mukabera, Charity (Kabale University, 2024)
The study research focused on the findings on the role of Faith-based organizations (FBOs) and the socio-economic impact of Covid 19 in Nyakinama Sub-county Kisoro district. The objectives of the study were to find out the services offered by FBO’s for the society in response to Covid 19 pandemic inNyakinama sub-county Kisoro district, to determine the effect of FBOs on increased rural incomes in Nyakinama sub-county Kisoro district and to explore the challenges faced by FBO’s in transformation of rural areas response to Covid-19 pandemic in Nyakinama sub-county Kisoro district. In chapter two, there was a critical review of the issues that have been explored and studied both theoretically and empirically in the existing literature on Faith-based organizations as an independent variable and the socio-economic impact of COVID-19 on rural areas as the dependent variable. In chapter three this is where the methods of data collection were put into action. The research used both qualitative and quantitative methods of data collection and analysis. The research used simple random sampling techniques in collecting and analyzing data and was used to provide equal chances to the sample size. Purposive sampling was also used to collect data from respondents who participated in the study. In chapter four shows the findings of the study obtained from the field interpreting the results analyzing based on the specific objectives of the study and chapter five portrays the summary of findings, the study concludes that the FBOs in Nyakinama sub-county Kisoro district like to manifest themselves as advocates of social change. For bringing effective social change the first priority is to eradicate all kinds of discrimination in society, empowerment of women is the first thing to do. No doubt, the poorest women are the most disadvantaged section of society, especially because they do not have access to information and resources. So they are lagging behind in the process of development. FBOs would like to involve these women and enhance their participation in the development process and the study also recommends that FBOs work together with the government counterparts who have done tremendous work. Many FBOs have not only grown up in size but have also developed infrastructures for research, training, and demonstration of alternative methods for increasing rural income. There are a number of successful FBOs who have actively participated in the development of society by creating employment opportunities and livelihood for the poor section of the society on the Faith-based organizations (FBOs) and the socio-economic impact of Covid 19 pandemic in Nyakinama Sub-county Kisoro district.